Submandibular Tumefaction with Unexpected Diagnosis - Guimarães, Géssyca Moreira Melo de Freitas; Manzano, Brena Rodrigues; Ferreira Júnior, Osny; Santos, Paulo Sérgio da Silva (ARCHIVES OF HEALTH INVESTIGATION, 2022)
Objective: Reporting the case of a 68-year-old patient, referred for evaluation of a possible odontogenic tumor. The patient had a submandibular nodule with 2-year evolution, approximately 2 cm, hardened, mobile and asymptomatic in the right submandibular region. After careful clinical examination and panoramic radiography analysis, the presumptive diagnosis was sialolith. Then, surgical removal was performed without complications and, after histopathological analysis, the clinical diagnosis was confirmed. Conclusion: Clinical, radiographic and histological evaluations are always a challenge for the correct diagnosis of hard lesions in the oral cavity.